Unusual Maxillary First Molars with C-Shaped Morphology on the Same Patient: Variation in Root Canal Anatomy - Naji Kharouf; Youssef Haïkel; Davide Mancino (Hindawi Limited, 2019)
A maxillary first molar should be considered a four-canal tooth until proved otherwise; however, a clinician should also be aware of the possibility of the presence of C-shaped root canal configuration with or without possibility of splitting into two or three canals. The two clinical cases reported in this paper describe the endodontic treatment of two maxillary first molars, on the same patient, with uncommon anatomy: the first case is about a maxillary first molar with only one C-shaped root and one oval canal with a large buccolingual diameter, a C1 type according to Fan's classification; the second case, about the contralateral maxillary first molar, is probably the first case documented of a maxillary first molar with a C-shaped root canal and C-shaped root with complete fusion of the three roots, having a C3 configuration.